KAJIAN POTENSI WISATA DESA KARTIKAJAYA KABUPATEN KENDAL DALAM PENYUSUNAN MODEL DAYA TARIK WISATA EKONOMI KREATIF - Nina Mistriani; Krisnawati Setyaningrum (Universitas Merdeka Malang, 2021)
This activity aims to study and improve the development of village tourism potential in the formulation of a creative economy tourism model in Kartikajaya Village, Kendal Regency, Central Java. The unemployment rate in this district is quite high, at 6%. It is greater than the unemployment rate in Central Java, which is 4.5% (Bappeda Central Java Province, 2019). This research is an action research conducted by mapping the tourism potential in Kartikajaya Village based on creative economy through the study of tourism potential and the preparation of community creativity. The creative economy provides skills and an alternative source of income through tourism around Kartikajaya Village. The data collection method used interviews with informants with a sample of 20 people (the Tourism Office, Industry Service, PKK, UMKM, Youth Organization, Pokdarwis, communities, and tourists), direct observation to the field, documents, and through FGD (Focus Group Discussion). The results of research by researchers on the aspect of internal strength come from the potential for tourist attraction and the creative economy. Meanwhile, the external analysis is a study of the potential for tourism to the community's economy, namely entrepreneurial opportunities, job opportunities, tourism supporting factors, and regional economic development drivers. This weakness occurs at the level of human resources who do not have training / skills in the tourism sector.